Paracoccidoides brasiliensis 30 kDa Adhesin: Identification as a 14-3-3 Protein, Cloning and Subcellular Localization in Infection Models - Silva, Julhiany de Fatima da [UNESP]; Oliveira, Haroldo César de [UNESP]; Marcos, Caroline Maria [UNESP]; Silva, Rosângela Aparecida Moraes da [UNESP]; Costa, Tania Alves da; Calich, Vera Lucia García; Almeida, Ana Marisa Fusco [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Public Library of Science (PLoS), 2013)
Paracoccidoides brasiliensis adhesion to lung epithelial cells is considered an essential event for the establishment of infection and different proteins participate in this process. One of these proteins is a 30 kDa adhesin, pI 4.9 that was described as a laminin ligand in previous studies, and it was more highly expressed in more virulent P. brasiliensis isolates. This protein may contribute to the virulence of this important fungal pathogen. Using Edman degradation and mass spectrometry analysis, this 30 kDa adhesin was identified as a 14-3-3 protein. These proteins are a conserved group of small acidic proteins involved in a variety of processes in eukaryotic organisms. However, the exact function of these proteins in some processes remains unknown. Thus, the goal of the present study was to characterize the role of this protein during the interaction between the fungus and its host. To achieve this goal, we cloned, expressed the 14-3-3 protein in a heterologous system and determined its subcellular localization in in vitro and in vivo infection models. Immunocytochemical analysis revealed the ubiquitous distribution of this protein in the yeast form of P. brasiliensis, with some concentration in the cytoplasm. Additionally, this 14-3-3 protein was also present in P. brasiliensis cells at the sites of infection in C57BL/6 mice intratracheally infected with P. brasiliensis yeast cells for 72 h (acute infections) and 30 days (chronic infection). An apparent increase in the levels of the 14-3-3 protein in the cell wall of the fungus was also noted during the interaction between P. brasiliensis and A549 cells, suggesting that this protein may be involved in host-parasite interactions, since inhibition assays with the protein and this antibody decreased P. brasiliensis adhesion to A549 epithelial cells. Our data may lead to a better understanding of P. brasiliensis interactions with host tissues and paracoccidioidomycosis pathogenesis. © 2013 Silva et al.
Keywords: adhesin; protein 14 3 3; animal experiment; animal model; animal tissue; antibody production; cell adhesion; cellular distribution; colony forming unit; controlled study; disease model; fungal cell wall; fungus; gene sequence; heterologous expression; host pathogen interaction; immunocytochemistry; in vitro study; in vivo study; mass spectrometry; molecular cloning; mouse; mycosis; nonhuman; nucleotide sequence; Paracoccidoides brasiliensis; pathogenesis; protein determination; protein function; protein localization; protein purification; sequence homology; South American blastomycosis